Ionosphere-magnetosphere energy interplay in the regions of diffuse aurora - Khazanov G.V.; Glocer A.; Sibeck D.G.; Tripathi A.K.; Detweiler L.G.; Avanov L.A.; Singhal R.P. (My University, 2025)
Both electron cyclotron harmonic (ECH) waves and whistler mode chorus waves resonate with electrons of the Earth's plasma sheet in the energy range from tens of eV to several keV and produce the electron diffuse aurora at ionospheric altitudes. Interaction of these superthermal electrons with the neutral atmosphere leads to the production of secondary electrons (E < 500–600 eV) and, as a result, leads to the activation of lower energy superthermal electron spectra that can escape back to the magnetosphere and contribute to the thermal electron energy deposition processes in the magnetospheric plasma. The ECH and whistler mode chorus waves, however, can also interact with the secondary electrons that are coming from both of the magnetically conjugated ionospheres after they have been produced by initially precipitated high-energy electrons that came from the plasma sheet. After their degradation and subsequent reflection in magnetically conjugate atmospheric regions, both the secondary electrons and the precipitating electrons with high (E > 600 eV) initial energies will travel back through the loss cone, become trapped in the magnetosphere, and redistribute the energy content of the magnetosphere-ionosphere system. Thus, scattering of the secondary electrons by ECH and whistler mode chorus waves leads to an increase of the fraction of superthermal electron energy deposited into the core magnetospheric plasma. Published 2016. This article is a US Government work and is in the public domain in the United States of America.